Hormone-Induced Calcium Oscillations Depend on Cross-Coupling with Inositol 1,4,5-Trisphosphate Oscillations - Gaspers, Lawrence D. (Cell Rep, 2014)
Receptor-mediated oscillations in cytosolic Ca(2+) concentration ([Ca(2+)](i)) could originate either directly from an autonomous Ca(2+) feedback oscillator at the inositol 1,4,5-trisphosphate (IP(3)) receptor or as a secondary consequence of IP(3) oscillations driven by Ca(2+) feedback on IP(3) metabolism. It is challenging to discriminate these alternatives, because IP(3) fluctuations could drive Ca(2+) oscillations or could just be a secondary response to the [Ca(2+)](i) spikes. To investigate this problem, we constructed a recombinant IP(3) buffer using type-I IP(3) receptor ligand-binding domain fused to GFP (GFP-LBD), which buffers IP(3) in the physiological range. This IP(3) buffer slows hormone-induced [IP(3)] dynamics without changing steady-state [IP(3)]. GFP-LBD perturbed [Ca(2+)](i) oscillations in a dose-dependent manner: it decreased both the rate of [Ca(2+)](i) rise and the speed of Ca(2+) wave propagation and, at high levels, abolished [Ca(2+)](i) oscillations completely. These data, together with computational modeling, demonstrate that IP(3) dynamics play a fundamental role in generating [Ca(2+)](i) oscillations and waves.